The contrast medium volume to estimated glomerular filtration rate ratio as a predictor of contrast-induced nephropathy after primary percutaneous coronary intervention - Liu, Yong; Tan, Ning; Zhou, Ying-Ling; He, Peng-Cheng; Luo, Jian-Fang; Chen, Ji-Yan (International urology and nephrology, 2012)
Background Contrast-induced nephropathy (CIN) is a serious complication in percutaneous coronary intervention (PCI) patients, which may be related to the contrast dose used during cardiac catheterization. Methods We prospectively investigated 277 consecutive consenting patients with acute ST-segment elevation myocardial infarction (STEMI) who were given primary PCI, and we calculated their ratio of volume of contrast media to estimated glomerular filtration rate (V/eGFR). Receiver–operator characteristic methods were used to identify the optimal sensitivity for the observed range of V/eGFR for CIN (i.e., within 48–72 h). The predictive value of V/eGFR for the risk of CIN was assessed using multivariable logistic regression. Results Twenty-five (9%) patients developed CIN. The baseline mean and median V/eGFR values were significantly greater among patients with CIN (mean 3.22 ± 1.53, median 2.97, and interquartile range 1.90–4.17) than among those without CIN (mean 1.80 ± 1.00, median 1.52, and interquartile range 1.12–2.21, P < 0.001). The receiver–operator characteristic curve analysis indicated that a V/eGFR ratio of 2.39 was a fair discriminator for CIN (C statistic 0.81). After adjusting for other known predictors of CIN, a V/eGFR ratio ≥ 2.39 remained significantly associated with CIN (odds ratio 4.24, 95% confidence interval 1.23–14.66, P < 0.05). Conclusion A V/eGFR ratio ≥ 2.39 was a significant and independent predictor of CIN after primary PCI in patients with STEMI.